The Evolution of Enterprise Reform in Africa: From State-owned Enterprises to Private Participation in Infrastructure - and Back? - John Nellis (Fondazione Eni Enrico Mattei (FEEM), 2005)
Many African state-owned enterprises (SOEs), particularly those in infrastructure, have a long history of poor performance. From the outset, SOE financial and economic performance generally failed to meet the expectations of their creators and funders. By the late 1970s, the situation was alarming, and by early 1980s, critical. The poor financial performance of SOEs became so burdensome to government budgets that it attracted the attention of the international financial institutions, or IFIs. In response, in the 1980s, the World Bank approved SOE reforms that could be summed up in the term commercialization. By the mid-1990s, however, the idea of making SOEs function efficiently and effectively under government management was largely abandoned by the IFIs and privatization and private participation in infrastructure, or PPI became the order of the day. Once more, however, the results were disappointing. PPI has not been as widely adopted as anticipated, nor has it generated the massive resources and changes hoped for, nor has it been widely accepted as beneficial by the African public. The findings of recent studies in Africa suggest that PPI should not be jettisoned, and that the more productive path is to recognize the limitations of the approach, and to work harder at creating the conditions needed to make it function effectively. This will entail, as many have recognized, an end to the view that public and private infrastructure provision is a dichotomy a case of either-or, one or the other and a better appreciation of the extent to which the performance of each is dependent on the competence of the other. In other words, for the private sector to perform well, public sector capacity must be enhanced. Moreover, proposed tactics of reform should fit more closely with the expectations and sentiments of the affected government, consumer base, and general population. This broader approach implies, probably, a reduction in the scope and, certainly, a reduction in the planned speed of operations. Improving infrastructure performance is a long-term matter.
Keywords: F3; L3; N17; N27; N47; N77; O55; 330; Africa; Enterprise reform; State-owned enterprises; Privatization; Öffentliches Unternehmen; Privatisierung; Afrika südlich der Sahara